2018
DOI: 10.1038/s41385-018-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bacterial metabolism by the microenvironment controls MAIT cell stimulation

Abstract: Mucosal-associated invariant T (MAIT) cells are abundant innate-like T lymphocytes in mucosal tissues and recognize a variety of riboflavin-related metabolites produced by the microbial flora. Relevant issues are whether MAIT cells are heterogeneous in the colon, and whether the local environment influences microbial metabolism thereby shaping MAIT cell phenotypes and responses. We found discrete MAIT cell populations in human colon, characterized by the diverse expression of transcription factors, cytokines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 45 publications
4
55
0
1
Order By: Relevance
“…We suggest that the MAIT cell activating potential of individual species, but also microbial communities, depends on the availability of riboflavin in the culture medium and on the culture conditions, which together determine the need for riboflavin biosynthesis. In support of this, culture conditions have recently been identified to alter the MAIT cell activating potential of E. coli (Schmaler et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…We suggest that the MAIT cell activating potential of individual species, but also microbial communities, depends on the availability of riboflavin in the culture medium and on the culture conditions, which together determine the need for riboflavin biosynthesis. In support of this, culture conditions have recently been identified to alter the MAIT cell activating potential of E. coli (Schmaler et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Finally, how Ags of differing affinity influence MAIT cell effector function is also unclear. A recent study, however, showed that activation of MAIT cells with Ags of weak, intermediate, or high potency induce differential changes in surface marker expression (58). This is reminiscent of what has been described for NKT cells in that TCR-mediated signaling events of different strength are capable of activating distinct transcriptional pathways and effector functions (54).…”
Section: Mait Cell Diversity-variation In An "Invariant" Populationmentioning
confidence: 84%
“…For example, exogenous IL-12/ 18 allows MAIT cells to produce IFN-g and respond to viral infections in the absence of TCR ligation (28,29), whereas MAIT cells in the liver (19) and female genital tract (65) are primed to produce IL-17 and also IL-22 in the latter. Likewise, MAIT cells in the colon differ substantially from their blood counterparts, expressing activation markers and inhibitory receptors and express higher levels of T-bet and RORgt, licensing stronger proinflammatory responses, in particular production of IFN-g and TNF (58). These characteristics may also allow MAIT cells to promote autoimmunity (66) and cancer (31), where dysregulated expression of innate cytokines can elicit an undesired MAIT cell effector response even in the absence of defined MAIT cell Ag.…”
Section: Mait Cell Diversity-variation In An "Invariant" Populationmentioning
confidence: 99%
“…Mutations in key enzymes of the riboflavin biosynthetic pathway in both Gram positive and negative bacteria can abrogate MAIT cell activation [33], [52]. Different bacteria that possess the riboflavin biosynthetic pathway induce varying levels of MAIT stimulation [36], [37], possibly through the influences of the microenvironment on bacterial metabolism and antigen availability, or the known short half-life of the potent MAIT cell antigens, 5-OP-RU and 5-OE-RU [53]. The ability of MAIT cells to recognise and respond to several isolates of the same pathogen may also vary to reflect bacterial metabolic differences.…”
Section: Discussionmentioning
confidence: 99%
“…While many commensal and pathogenic bacteria possess the riboflavin biosynthetic pathway, the levels of resulting MAIT stimulation varies [36], [37], perhaps reflecting the influence of microenvironment on bacterial metabolism and antigen availability. The ability of MAIT cells to recognise and respond to several isolates of the same pathogen may also vary depending on metabolic differences between isolates [38].…”
Section: Introductionmentioning
confidence: 99%